Mind and Sight: Seeing Beyond the Retina - Connecting the Dots in Relationships between Glaucoma and Earlier Diagnosis of Dementia: A Pilot Study (Medical Forum Monthly, 2024)
Objective: This pilot study aims to investigate the relationship between glaucoma and the earlier diagnosis of dementia, focusing on potential biomarkers and clinical implications.Study Design: Cohort Sectional StudyPlace and Duration of Study: This study was conducted at the Department of Ophthalmology FRPMC/Air University from August 2021 to August 2022.Methods: Dementia Patients from the neurological clinic will be referred to the eye department of FRPMC Karachi for ocular examination. Informed consent will be obtained from eligible individuals interested in participating. The research participants will be divided in to two groups each consists of 30 members, group 1= patients with dementia and group 2 normal age and sex matched controls.Results: Our results revealed significant correlations between specific retinal parameters and cognitive function in glaucoma patients. Reduced retinal nerve fiber layer thickness and macular ganglion cell complex thickness were associated with poorer cognitive performance, as indicated by lower scores on cognitive screening tests. Furthermore, structural changes in the retinal layers were observed to correlate with cognitive decline, suggesting potential utility as early indicators of dementia risk. These findings remained significant even after controlling for age, gender, education level, and ocular characteristics such as intraocular pressure and visual field status.Conclusion: This pilot study provides preliminary evidence supporting the association between glaucoma and dementia, highlighting the potential of retinal biomarkers as early indicators of cognitive impairment in glaucoma patients. The observed correlations between retinal parameters and cognitive function underscore the importance of ocular health in assessing overall cognitive status. These findings suggest the feasibility of incorporating routine retinal assessments into dementia screening protocols, enabling earlier detection and intervention. Further longitudinal studies are warranted to validate these findings and elucidate the underlying mechanisms driving the relationship between glaucoma and dementia, ultimately facilitating personalized approaches to patient care, and improving clinical outcomes.